Study on Selenium and Other Trace Elements Presents in Selenium-Enriched Strawberry by ICP-MS - Zhang, Yanbei; Zhang, Baojin; Rui, Yukui (Asian Journal of Chemistry, 2013)
Selenium, as an essential element for human health, plays an irreplaceable role on human aging and disease prevention. Selenium enriched agricultural products which are used as the best way to supplement selenium have wide prospect and are developing rapidly. However China haven't general standards about selenium enriched products and the quality of them is not uniform, selenium enriched products' sustainable development can't be achieved. By researching selenium enriched strawberries from four different greenhouses, we found the contents of selenium can be 2.58 to 8.87 times to common strawberries, which proved the selenium fertilizer is good. But the content of heavy metals in selenium-enriched strawberry exceeded the national standard, so we should pay attention to its food safety when eating selenium-enriched strawberry. Application of selenium fertilizer increased the content of Ca and Zn in strawberry, in which Ca can prevent the rotting fruit during storage and extend the fruit shelf. At the same time studies have shown that the combination of selenium and zinc antagonize cadmium hazards. It is recommended that we should develop national standards for selenium-enriched fruits and other agricultural products as soon as possible to secure food nutrition and food safety.